The cultural studies reader - During, Simon 1950- (Routledge, 1993)
"The Cultural Studies Reader" provides an introduction for students of this discipline. It presents a selection of influential and innovative essays in the field by writers such as Barthes, Adorno, Lyotard, Stuart Hall and Gayatri Spivak, with a succinct introduction to each. The book encompasses a wide range of topics, from sport to postmodernism, from museums to supermarkets, from gay writing to rock and roll, and covers every important cultural studies method and theory. The book can be used as much more than an introductory anthology: Simon During's introduction to the field surveys the history and development of cultural studies, from its origins in sociological analysis of post-war Britain to its present as a truly trans-national discipline. Looking at the future possibilities for cultural studies, he argues that cultural studies methodologies offer great potential for confronting such contemporary issues as postcolonialism, globalization and multiculturalism. -- Description from http://Amazon.com (Feb. 22, 2012